The Metaphoric Perceptions of Primary School Teachers on the Concept of Inspection - Toremen, Fatih; Dos, Izzet (Edam, 2009)
The aim of this study is to reveal the perceptions of primary school teachers on the concept of inspection with the help of metaphors. The data were obtained from randomdy selected students of 20 primary schools in the center of Gaziantep. 418 questionnaires were evaluated. The measurement instrument consisted of 31 metapbors and one open-ended question,which reads like the inspector is like... because... Statistical mean and dispersion, percentage, and frequency were studied. As a result of the study, the metaphors related to bow inspectors were perceived and the answers to the items of the questionnaire were commented. 123 metaphors were developed. The developed metaphors mainly consist of negative metaphors. In the study, 76 negative, 20 both positive and negative, and 8 metaphors indicating that there is no need for the inspectors were determined. Only 12 metaphors that had positive meanings were found. Anything was stated for seven metaphors or they were used with similar meanings.
Keywords: Inspector; Metaphor; Inspector Metaphors